DESIGNING INTERFACE OF MARKETPLACE BUILD ID MERCHANT ARCHITECT USING TASK-CENTERED SYSTEM DESIGN - Nabila Riska Ayu; Pacu Putra; Nabila Rizky Oktadini; Putri Eka Sevtiyuni; Allsela Meiriza (STMIK Royal, 2023)
Abstract: The advancement of information technology is progressively exerting significant impact across diverse aspects of life, including business. PT Semen Baturaja Tbk is developing a marketplace platform called Build Id to meet community's needs for high-quality construction materials and services, also aims to enhance company's product sales and brand recognition. A system with quality provides ease of use in order to achieve customer satisfaction. Build Id merchant for architects website requires user-friendly design recommendations to increase the user experience when it gets distributed to the market. To achieve this goal, Task-Centered System Design (TCSD) method is being used to focused the design process. TCSD is a method in Human Computer Interaction (HCI) used to identify task and user requirements. The method consists of 4 stages, namely, identification, user-centered requirements analysis, design through scenarios, and walkthrough evaluation. In this study, identification was carried out by conducting system observations and interviews with Build Id team at Digital Marketing Unit of PT Semen Baturaja Tbk and architect as the prospective system users. The interface design results were evaluated using System Usability Scale (SUS) and received final score of 69.615, indicating that the interface design made using TCSD method is feasible for users to use. Keywords: Interface; System Usability Scale; Task-Centered System Design Abstrak: Perkembangan teknologi informasi kian berpengaruh besar dalam berbagai bidang kehidupan, termasuk di dunia bisnis. PT Semen Baturaja Tbk mengembangkan suatu sistem dalam bentuk marketplace dengan nama Build Id, dengan tujuan untuk memenuhi kebutuhan bahan bangunan dan jasa konstruksi yang berkualitas bagi masyarakat, serta memperluas penjualan produk dan branding merk dari PT Semen Baturaja Tbk ini sendiri. Sistem yang berkualitas memberikan kemudahan dan kenyamanan dalam penggunaannya demi mewujudkan kepuasan pelanggan. Build Id merchant untuk arsitek memerlukan rekomendasi desain atau prototype user interface yang user friendly demi meningkatkan pengalaman pengguna ketika didistribusikan ke pasaran nantinya. Metode Task-Centered System Design (TCSD) digunakan untuk membantu proses perancangan lebih terarah. TCSD adalah metode dalam Human Computer Interaction (HCI) yang digunakan untuk mengidentifikasi kebutuhan task dan pengguna. Metode TCSD terdiri dari 4 tahap yaitu, identification, user-centered requirements analysis, design through scenario, dan walkthrough evaluation. Identifikasi dalam penelitian ini dilakukan dengan observasi dan wawancara bersama tim Build Id dan calon pengguna sistem yaitu arsitek. Hasil dari rancangan interface kemudian dievaluasi menggunakan System Usability Scale (SUS) dengan hasil skor akhir 69,615, menunjukkan rancangan interface yang dibuat dengan metode TCSD ini layak untuk digunakan pengguna. Kata kunci: Interface; System Usability Scale; Task-Centered System Design